Right ventricular failure due to subacute massive pulmonary embolism - Claudio Giumelli; Giacomo Bussolati; Patricia Granauro; Paolo Montanari (Italian Journal of Medicine)
We present a clinical case of right heart failure secondary to subacute pulmonary embolism, which was managed in our semi-intensive care unit. The case is accompanied by interesting iconography, including electrocardiogram, echocardiogram, ventilation-perfusion, pulmonary scintigraphy, and chest angio-computed tomography.